2020
DOI: 10.1038/s41598-020-71857-3
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the CCL2/CCR2 and CXCL10/CXCR3 axes contributes to antitumor effects in a mouse model of malignant glioma

Abstract: Glioblastoma multiforme involves glioma stem cells (GSCs) that are resistant to various therapeutic approaches. Here, we studied the importance of paracrine signaling in the glioma microenvironment by focusing on the celecoxib-mediated role of chemokines C–C motif ligand 2 (CCL2), C-X-C ligand 10 (CXCL10), and their receptors, CCR2 and CXCR3, in GSCs and a GSC-bearing malignant glioma model. C57BL/6 mice were injected with orthotopic GSCs intracranially and divided into groups administered either 10 or 30 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…In addition, MDR1 expression is associated with several cellular signaling pathways and protein kinases, chaperons, ubiquitin-related enzymes, and transcription factors. 31 As the COX-2 inhibitor induced apoptosis by inhibiting the AKT pathway in lowgrade glioma cells in a previous study, 18 we observed MDR1 down-regulation through the Akt/NF-kB pathway upon celecoxib treatment. Furthermore, we observed the down-regulation of MDR1 by a NF-kB inhibitor, CAPE.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, MDR1 expression is associated with several cellular signaling pathways and protein kinases, chaperons, ubiquitin-related enzymes, and transcription factors. 31 As the COX-2 inhibitor induced apoptosis by inhibiting the AKT pathway in lowgrade glioma cells in a previous study, 18 we observed MDR1 down-regulation through the Akt/NF-kB pathway upon celecoxib treatment. Furthermore, we observed the down-regulation of MDR1 by a NF-kB inhibitor, CAPE.…”
Section: Discussionsupporting
confidence: 54%
“…17 We also reported that a selective cyclooxygenase-2 (COX-2) inhibitor, celecoxib exerted anti-tumor effects associated with the down-regulation of Akt/NF-kB pathways in mouse glioma stem cells (GSCs) and GSCs-bearing glioma model. 18,19 Based on these ndings, we hypothesized that down-regulation of MDR1 by celecoxib via Akt/NF-kB pathways may promote the uptake of 5-ALA into GBM, thereby elevating cellular PpIX levels and enhance the anti-tumor effects of SDT.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…First, we confirmed that SDT monotherapy exerted anti-tumor effects in GSCs and GSCs-bearing glioma model; however, it displayed transient and limited efficacy. Since we have demonstrated the anti-tumor effects by a COX2 inhibitor, celecoxib 18 , 19 , we assessed the efficacy of SDT combined with pre-treatment by celecoxib. Expectedly, the pre-treatment by celecoxib decreased the expression of MDR-1 and elevated the cellular PpIX levels induced by 5-ALA, resulting in the enhanced anti-tumor effects of the combination therapy in the GSC-bearing glioma model.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported high expression of MDR1 in GBM and demonstrated that down-regulation of MDR1 via Akt/NF-κB pathways upon transfection of the Ad-DKK3 gene augmented the anti-tumor effects of temozolomide in GBM cells and in a GBM-xenograft model 17 . We also reported that a selective cyclooxygenase-2 (COX-2) inhibitor, celecoxib exerted anti-tumor effects associated with the down-regulation of Akt/NF-κB pathways in mouse glioma stem cells (GSCs) and GSCs-bearing glioma model 18 , 19 . Based on these findings, we hypothesized that down-regulation of MDR1 by celecoxib via Akt/NF-κB pathways may promote the uptake of 5-ALA into GBM, thereby elevating cellular PpIX levels and enhance the anti-tumor effects of SDT.…”
Section: Introductionmentioning
confidence: 99%
“…A recent immunohistochemical study found that CXCL10 was overexpressed in GBM [26]. Kenji Shono et al revealed that CXCL10 exerts anti-tumor impact in a mouse model of malignant glioma [27]. CXCL10 appears to be critical regulator of GBM growth and progression.…”
Section: Discussionmentioning
confidence: 99%